2015
DOI: 10.1364/ao.54.000912
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional high-speed and long-range tomography and profilometry using liquid-crystal Fabry–Perot resonator

Abstract: A two-dimensional high-speed, long-range tomography and profilometry based on a low-coherence optical interferometry has been developed. A liquid-crystal Fabry-Perot resonator is fabricated to be a low-coherence optical frequency comb generator for expanding the measurement depth of the tomography and profilometry. The line-shape interference fringes with the individual fringe orders are obtained by a CCD camera in real time. The relative optical length, corresponding to the sample depth information, can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Surface profilometry and tomography based on either time-domain interferometry [1][2][3] or frequency-domain interferometry [4][5][6] have advantages of high resolution, noncontact, and are nondestructive for industrial applications. 2D single-shot cross-sectional imaging based on optical interferometry [7][8][9][10][11][12] is helpful for measuring the surface profile of moving objects in industrial production lines. In conventional point scanning interferometry [13][14][15] to obtain cross-sectional information along the axial and lateral axes, the object is required to be fixed because the vibration of the object affects the quality of the 2D image, which needs to distinguish the fine shapes of the object.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface profilometry and tomography based on either time-domain interferometry [1][2][3] or frequency-domain interferometry [4][5][6] have advantages of high resolution, noncontact, and are nondestructive for industrial applications. 2D single-shot cross-sectional imaging based on optical interferometry [7][8][9][10][11][12] is helpful for measuring the surface profile of moving objects in industrial production lines. In conventional point scanning interferometry [13][14][15] to obtain cross-sectional information along the axial and lateral axes, the object is required to be fixed because the vibration of the object affects the quality of the 2D image, which needs to distinguish the fine shapes of the object.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult to utilize conventional point scanning interferometry for detecting defects on moving objects in industrial production lines, where the objects are moved, and vibration occurs. In order to overcome this problem, a 2D single-shot imaging system based on time-domain interferometry [7][8][9][10][11][12] is a potential solution because the axial and lateral information can be simultaneously and directly obtained within the shutter speed (or exposure time) of a 2D image sensor. Therefore, in a 2D single-shot imaging system, a fast shutter speed is required to measure the defects on moving objects for industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…It remains a challenge to achieve both real-time and long-range operations for tomography and profilometry. To over this issue, in our previous reports [3,4,5] , we proposed the single-shot tomography and profilometry using a broadband lightsource in 1.5 μm window and spatial phase modulation technology. These systems can measure both depth and surface profile of the quasi-transparent samples.…”
Section: Introductionmentioning
confidence: 99%
“…Realtime tomogram images were seen by a conventional 2D NIR CCD camera with a resolution of 11 μm (for tomography) and 2.7 μm (for profilometry). In these systems, together with the single-shot operation, we considered how to extend the measurement range of the tomography and profilometry by using different optical components such as the vitally imaged phased array (VIPA) [3] , or the Fabry-Perot cavity [4] , or the Liquid-Crystal resonator [5] . It was confirmed that the measurement range of our proposed singleshot tomography could be expanded to approximate 30 mm, and the resolution of the systems is not changed over the expanded measurement range because the resolution of those systems depends on only the bandwidth of the broadband lightsource.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation